Neurological Manifestations in Pediatric COVID-19 Patients Hospitalized at King Abdulaziz University Hospital, Jeddah, Saudi Arabia: A Retrospective Study - Moustafa A. Hegazi; Fajr A. Saeedi; Ali F. Atwah; Mohamed H. Sayed; Asala A. Albeladi; Shahad B. Alyoubi; Razan A. Aljudibi; Shahad M. Alyaslami; Abdullah T. Alkathiry; Abobakr A. Abdelgalil (MDPI AG, 2022)
There are limited data about neurological manifestations in pediatric COVID-19 patients from all over the world, including Saudi Arabia. This study was performed to identify characteristics of pediatric COVID-19 cases with neurologic involvement hospitalized at King Abdulaziz University Hospital (KAUH), Saudi Arabia. This retrospective cross-sectional study included hospitalized patients aged 0-19 years with confirmed SARS-CoV-2 from April 2020 to February 2022. The required data were retrieved from patients' medical records. Ninety-four cases were included. The median ages of the studied group, those with neurological manifestations, and those without neurologic manifestations, were 6.5, 11.0, and 5.0 years, respectively. Neurological manifestations occurred in 29 COVID-19 patients (30.9%) with headache and decreased consciousness being the most common recorded manifestations in 8.5% and 6.4% of patients, respectively. Specific neurological manifestations were rare, as only two infants developed encephalopathy with fatal outcome. Most patients with and without neurological manifestations survived. Neuroimaging abnormalities were detected in 8 cases with neurological manifestations. Neurological manifestations were common in 31% of hospitalized pediatric COVID-19 cases. However, most of the neurological manifestations were mild and nonspecific, with headache being the most common one. Specific neurological manifestations were rare; however, pediatric COVID-19 patients, particularly young infants, were at risk of developing severe encephalopathy with fatal outcome.